Icon Design For Artifact Collection Classification At The Sri Baduga Museum, Bandung - Martha Tisna Ginanjar Putri; Iis Purnengsih; Winny Gunari Widya Wardani; Nazwa Vina Ayudyasari; Andaru Raisya Hartono (International Journal of Arts Architecture & Design)
The Sri Baduga Museum, established as the Technical Implementation Unit of the Tourism and Culture Office of West Java Province, was named in 1990 to honor Sri Baduga Maharaja, the Sunda King who ruled the Tatar Sunda region from 1482 to 1521. The Museum has ten classifications of historical artifacts from Sundanese, starting from prehistoric times to the colonial era. However, the classification has not had visual signs. This condition is a research gap for researchers to create iconic signs that visually convey ten collections of artifact museums. This study adopts quantitative and qualitative approaches. The collection of data is started by conducting a survey of young people to know their perspective of the museum’s collection. A visual communication approach was applied to develop iconic signs based on design elements: line, shape, space, colour, and texture. Icon design aims to represent the museum’s artifact classifications which consists of Geology, Numismatics, Biology, Philology, Ethnography, Ceramology, Archaeology, Fine Arts, History, and Technology. This research hopes that this icon design can contribute to Sri Baduga Museum according to the museum’s need. It is also hoped that this icon design can become a reference for other museums in developing information.